Hunting for common ground between wildlife governance and commons scholarship. Issue 1 (24th October 2018) - Smith, Hillary; Marrocoli, Sergio; Garcia Lozano, Alejandro; Basurto, Xavier
Abstract: Wildlife hunting is essential to livelihoods and food security in many parts of the world, yet present rates of extraction may threaten ecosystems and human communities. Thus, governing sustainable wildlife use is a major social dilemma and conservation challenge. Commons scholarship is well positioned to contribute theoretical insights and analytic tools to better understand the interface of social and ecological dimensions of wildlife governance, yet the intersection of wildlife studies and commons scholarship is not well studied. We reviewed existing wildlife‐hunting scholarship, drawing on a database of 1, 410 references, to examine the current overlap with commons scholarship through multiple methods, including social network analysis and deductive coding. We found that a very small proportion of wildlife scholarship incorporated commons theories and frameworks. The social network of wildlife scholarship was densely interconnected with several major publication clusters, whereas the wildlife commons scholarship was sparse and isolated. Despite the overarching gap between wildlife and commons scholarship, a few scholars are studying wildlife commons. The small body of scholarship that bridges these disconnected literatures provides valuable insights into the understudied relational dimensions of wildlife and other overlapping common‐pool resources. We suggest increased engagement among wildlife and commons scholars and practitioners to improve the state of knowledge and practice of wildlife governance across regions, particularly for bushmeat hunting in the tropics, which is presently understudied through a common‐pool resource lens. Our case study of the Republic of Congo showed how the historical context and interrelationships between hunting and forest rights are essential to understanding the current state of wildlife governance and potential for future interventions. A better understanding of the interconnections between wildlife and overlapping common‐pool resource systems may be key to understanding present wildlife governance challenges and advancing the common‐pool resource research agenda. Abstract : Article impact statement : Wildlife hunting and commons scholarship are largely disconnected yet their mutual utility can help solve wildlife‐governance dilemmas. Abstract : En Búsqueda de Terreno Común entre la Gobernanza de Fauna y el Conocimiento sobre Bienes Comunes Resumen: La caza de fauna es esencial para el sustento y la seguridad alimentaria en muchas partes del mundo pero presenta tasas de extracción que podrían amenazar a los ecosistemas y a las comunidades humanas. Por esto, gobernar el uso sustentable de la fauna es un dilema social importante y un reto para la conservación. El conocimiento sobre los bienes comunes está bien posicionado para contribuir con ideas teóricas y herramientas analíticas para un mejor entendimiento de la interfaz entre las dimensiones sociales y ecológicas de la gobernanza de fauna, aunque la intersección de los estudios sobre fauna y el conocimiento sobre los bienes comunes no esté bien estudiada. Revisamos el conocimiento existente sobre la caza de fauna a partir de una base de datos de 1, 410 referencias para examinar el traslape actual con el conocimiento sobre los de bienes comunes por medio de múltiples métodos, incluyendo el análisis de redes sociales y la codificación deductiva. Encontramos que una proporción muy pequeña de estudios de fauna incorporaban marcos de trabajo y teorías de bienes comunes. La red social de conocimiento sobre la fauna tenía una interconexión muy densa con varios grupos de publicaciones importantes, mientras que la del conocimiento de bienes de fauna era escasa y estaba aislada. A pesar del enorme vacío entre el conocimiento de bienes y la fauna, algunos están estudiando los bienes de fauna. El pequeño cuerpo de becas que construye un puente entre estas literaturas desconectadas proporciona ideas valiosas sobre la dimensión de las relaciones poco estudiadas de la fauna y otros recursos comunes que se traslapan. Sugerimos una participación mayor entre el conocimiento de fauna y bienes comunes y los practicantes para mejorar el estado de conocimiento y de las prácticas de la gobernanza de fauna a lo largo de todas las regiones, particularmente para la caza de fauna en los trópicos, la cual actualmente está poco estudiada dentro de la visión de los recursos comunes. Nuestro estudio de caso sobre la República del Congo mostró cómo el contexto histórico y las interrelaciones entre la caza y los derechos de bosque son esenciales para el entendimiento del estado actual de la gobernanza de fauna y el potencial para las futuras intervenciones. Un mejor entendimiento de las interconexiones entre la fauna y los sistemas de recursos comunes que se traslapan puede ser una clave para entender los retos actuales de la gobernanza de fauna y el avance de la agenda de investigación sobre los recursos comunes. 摘要: 在世界上很多地方, 野生动物狩猎对人们的生计和食物保障至关重要, 但目前狩猎的速率可能威胁到生态系统和人类社会。因此, 野生动物资源可持续利用的管理是重要的社会困境和保护挑战。公共资源的学术研究有助于提供深入的理论认识和分析工具, 来更好地理解野生动物管理中社会和生态维度的交界, 然而, 野生动物研究和公共资源研究的交叉点还没有得到深入探索。我们借助于一个含有 1, 410 篇参考文献的数据库, 回顾了现有野生动物狩猎的知识, 并通过包括社会网络分析和演绎编码在内的多种方法分析其与公共资源研究的重叠。我们发现, 只有很少一部分的野生动物研究纳入了公共资源的理论和框架。野生动物研究的社会网络与几个主流出版物集群紧密相连, 而野生动物公共资源研究则稀少且孤立。尽管野生动物与公共资源的研究之间存在巨大差距, 但仍有一些学者在研究野生动物公共资源。这一小部分学术研究将一些关系不紧密的文献联系起来, 为理解野生动物和其它重叠的公共资源的关系提供了宝贵的见解。我们建议加强野生动物和公共资源学者和管理实践者之间的交流, 来提高各地区野生动物管理的知识和实践水平, 特别是目前从公共资源角度研究较少的热带地区丛林肉狩猎问题。我们对刚果共和国的案例研究表明了狩猎和林权之间的历史背景和相互关系在了解目前野生动物管理状态和未来干预措施的潜力中起到重要作用。更好地理解野生动物和重叠的公地资源系统的相互关系可能是理解野生动物管理目前面临的挑战和推进公地资源研究议程的关键。【翻译: 胡怡思; 审校: 聂永刚】